PENEGAKAN KODE ETIK NOTARIS DI ORGANISASI IKATAN NOTARIS INDONESIA DAERAH ISTIMEWA YOGYAKARTA - , Shelly Yeneda ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The research aims at identifying and analyzing the implementation of notary code of ethics enforcement performed by Indonesian Notary Association (INI) in Special Region of Yogyakarta as well as the obstacles faced by INI in enforcing the notary code of ethics particularly in Special Region of Yogyakarta. The research adopts juridical empiric al method. Data employed in the research are primary and secondary data. Secondary data are obtained from library study, while primary data are gained through interview with informants and respondents from the office of Ministry of Law and Human Rights, notary, and the officials of INI for Special Region of Yogyakarta. The research adopts qualitative analysis method, which enable s the researcher to analyze the data obtained qualitatively and to present the results descriptively. In withdrawing the conclusion, deductive method of thought is applied, which is concluding the specific research findings. Based on this method, vivid and inclusive description on the suitability of conceptual bases used under the research title can be obtained. The enforcement of notary code of ethics in Special Region of Yogyakarta by INI, which is performed by Honorary Board as the extension of INI, has been going well but less effective. This is due to indistinct grant of sanction which results in less optimum enforcement of unbalanced code of ethics with the great number of notary, lack of etiquette and ethic among the notaries themselves, lack of communication with the organization, and financial needs. The obstacles in enforcing notary code of ethics are the great number of the members of Honorary Board of Notary, particularly in Special Region of Yogyakarta, who become the members of Honorary Board only to cover up their ignorance of notary code of ethics and the vague and indistinct provision of information which complicates the investigation on code of ethics violation. In other words, reluctance among the notaries can hinder the enforcement of notary code of ethics.